MODERASI BERAGAMA DALAM SUDUT PANDANG KRISTIANI DAN IMPLEMENTASINYA DALAM KEHIDUPAN MASA KINI - Elditrisne Grace; Resiana; Herlina Tappi; Nober Pasang; Desi Limbong Kadang (Pondok Pesantren Baitul Qur`an Sambas, 2024)
This research examines the concept of religious moderation from a Christian perspective and its implementation in contemporary life. The primary focus of the study is to understand the values of religious moderation such as love, tolerance, and appreciation of religious diversity, based on the teachings and example of Jesus Christ. The method of literature review is used to explore theological literature, academic works, and church practices that illustrate the application of religious moderation in various contexts. The findings indicate that religious moderation is not only crucial for fostering harmony within the Christian community but also for promoting interfaith peace in an increasingly complex and diverse world. Challenges in implementing religious moderation include extremism, interreligious misunderstanding, and internal theological conflicts. However, opportunities to strengthen interfaith dialogue, build social cohesion, and promote universal values such as social justice and humanitarianism are also abundant. Therefore, this research provides not only a theoretical foundation on religious moderation in the Christian context but also practical recommendations for applying these values in everyday life, making the Christian community a positive agent of change towards a more inclusive and harmonious society.